Nutritional Analysis of Avocado Seed Flour Nuggets in Reducing Stunting - Eliska; Dur, Sajaratud (Window of Health : Jurnal Kesehatan, 2025)
Stunting is a condition where the growth of children under five is hampered due to a continuous lack of nutritional intake, which results in their height not being appropriate for their age. The short-term impact of stunting is increased morbidity and mortality rates, impaired growth, and increased burden of care and treatment costs. This study aimed to analyze about the nutritional value contained in avocado seed flour nuggets with chicken, catfish, and shrimp variants, especially the protein and calcium content. This study uses two research methods, namely descriptive and experimental methods. The aim of the descriptive method in this research was to explain the results of the nutritional content in avocado seed flour nuggets. The experimental method used in this research was to determine the nutritional content of protein and calcium in avocado seed flour at the Medan Center for Standardization and Industrial Services Laboratory using the Atomic Absorption Spectroscopy (AAS) method, referring to the SNI 01-2891-1992 procedure. Laboratory tests revealed the highest protein content in the chicken variant at 11.1%, followed by the shrimp variant at 10.3%, and the catfish variant at 9.57%. Meanwhile, the highest calcium (Ca) content was found in the catfish variant at 408 mg/kg, shrimp at 227 mg/kg, and chicken at 45.3 mg/kg.. Based on the results of nutritional content testing at the Medan Research and Standardization Center, the amount of protein and calcium content of avocado seed flour nuggets can meet 20% of the protein and calcium needs of toddlers.